2019 IEEE Radar Conference (RadarConf) 2019
DOI: 10.1109/radar.2019.8835744
|View full text |Cite
|
Sign up to set email alerts
|

Radar Communications for Combating Mutual Interference of FMCW Radars

Abstract: Commercial automotive radars used today are based on frequency modulated continuous wave signals due to the simple and robust detection method and good accuracy. However, the increase in both the number of radars deployed per vehicle and the number of such vehicles leads to mutual interference, cutting short future plans for autonomous driving and active safety functionality. We propose and analyze a radar communication (RadCom) approach to reduce this mutual interference while simultaneously offering communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
1
23
0
1
Order By: Relevance
“…The simulations are observed to exactly match analysis in (14). A verification of the vulnerable period for various victim-interferer distances is also presented in [35].…”
Section: Propositionmentioning
confidence: 57%
See 1 more Smart Citation
“…The simulations are observed to exactly match analysis in (14). A verification of the vulnerable period for various victim-interferer distances is also presented in [35].…”
Section: Propositionmentioning
confidence: 57%
“…It was shown that consideration of higher layers improved both radar and communication capabilities compared to coexistence studies focusing solely on the physical layer [17]. The analysis of the R2R interference conducted in [35], showed that higher-layer coordination of automotive radars through communications decreased R2R interference for two facing radars, whereas the same RadCom system was shown to increase the probability of detection of vulnerable road users by eliminating ghost targets [36]. This article complements these two previous studies by a comprehensive explanation of the method in large scale networks by the added functionality of self-interference mitigation among radars mounted on the same vehicle.…”
Section: Related Workmentioning
confidence: 99%
“…One approach to combat those problems is to add communication abilities to the radar, e.g. as in [2]. The authors propose to add an OFDM-based communication system to a FMCW-based radar by using frequencydivision multiplexing.…”
Section: Introductionmentioning
confidence: 99%
“…The interference problem in automotive radar scenarios has been addressed in many studies [9][10][11][12][13][14][15]. In [9], the authors addressed interference mitigation in automotive radars using pseudo-random cyclic orthogonal sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the work in [11] also proposed an approach for mutual interference mitigation between automotive radars based on frequency modulated continuous wave chirp diversity. The author of [12] presented a radar communications approach that was able to reduce the mutual interference between vehicles while offering a communication functionality in addition to the sensing function. Furthermore, the performance comparison of different mutual automotive radar interference mitigation algorithms was addressed in [13].…”
Section: Introductionmentioning
confidence: 99%